Investigating the Transcriptome of Candida albicans in a Dual-Species Staphylococcus aureus Biofilm Model - Short, Bryn; Delaney, Christopher; McKloud, Emily; Brown, Jason L.; Kean, Ryan; Litherland, Gary J.; Williams, Craig; Martin, S. Lorraine; MacKay, William G.; Ramage, Gordon (Frontiers in Cellular and Infection Microbiology, 2021)
Candida albicans is an opportunistic pathogen found throughout multiple body sites and is frequently co-isolated from infections of the respiratory tract and oral cavity with Staphylococcus aureus. Herein we present the first report of the effects that S. aureus elicits on the C. albicans transcriptome. Dual-species biofilms containing S. aureus and C. albicans mutants defective in ALS3 or ECE1 were optimised and characterised, followed by transcriptional profiling of C. albicans by RNA-sequencing (RNA-seq). Altered phenotypes in C. albicans mutants revealed specific interaction profiles between fungus and bacteria. The major adhesion and virulence proteins Als3 and Ece1, respectively, were found to have substantial effects on the Candida transcriptome in early and mature biofilms. Despite this, deletion of ECE1 did not adversely affect biofilm formation or the ability of S. aureus to interact with C. albicans hyphae. Upregulated genes in dual-species biofilms corresponded to multiple gene ontology terms, including those attributed to virulence, biofilm formation and protein binding such as ACE2 and multiple heat-shock protein genes. This shows that S. aureus pushes C. albicans towards a more virulent genotype, helping us to understand the driving forces behind the increased severity of C. albicans-S. aureus infections.